2013
DOI: 10.3748/wjg.v19.i29.4679
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic arterial infusion chemotherapy in hepatocellular carcinoma with portal vein tumor thrombosis

Abstract: AIM:To evaluate the prognostic factors and efficacy of hepatic arterial infusion chemotherapy in hepatocellular carcinoma with portal vein tumor thrombosis. METHODS:Fifty hepatocellular carcinoma (HCC) patients with portal vein tumor thrombosis (PVTT) were treated using hepatic arterial infusion chemotherapy (HAIC) via a subcutaneously implanted port. The epirubicin-cisplatin-5-fluorouracil (ECF) chemotherapeutic regimen consisted of 35 mg/m 2 epirubicin on day 1, 60 mg/m 2 cisplatin for 2 h on day 2, and 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 34 publications
4
43
1
Order By: Relevance
“…A recent report of HAIC monotherapy found complete and partial response rates of 4 and 36.5%, respectively, in 476 patients with advanced HCC including portal vein invasion [12] . In reports of approximately 50 HCC patients with PVTT, 6-8% of patients achieved a complete response, and 32-48% of patients had a partial or complete response [13,14] . The relatively high response rate to HAIC indicates that it may be more potent than sorafenib, despite any evidence of effectiveness.…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent report of HAIC monotherapy found complete and partial response rates of 4 and 36.5%, respectively, in 476 patients with advanced HCC including portal vein invasion [12] . In reports of approximately 50 HCC patients with PVTT, 6-8% of patients achieved a complete response, and 32-48% of patients had a partial or complete response [13,14] . The relatively high response rate to HAIC indicates that it may be more potent than sorafenib, despite any evidence of effectiveness.…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…However, HAIC was effective in a subset of patients, resulting in a complete response in 4-8% of patients, and an overall response rate (including complete and partial responses) of approximately 40% in patients with advanced HCC with portal vein invasion [12][13][14] . No complete responses and a small number of partial responses were reported in the 2-phase III sorafenib trials [7,15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PVTT often leads to extensive spreading of the tumor and can increase portal venous blood pressure, resulting in the fatal rupture of esophageal varices (33). PVTT can also decrease portal flow that may lead to ascites, jaundice, hepatic encephalopathy, or liver failure (33). Therefore, the presence of PVTT is one of the most significant prognostic factors of poor outcome (34,35), and it has been reported that these patients survive only 2.7-4 months if left untreated (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…PVTT often leads to extensive spreading of the tumor and can increase portal venous blood pressure, resulting in the fatal rupture of esophageal varices (33). PVTT can also decrease portal flow that may lead to ascites, jaundice, hepatic encephalopathy, or liver failure (33).…”
Section: Discussionmentioning
confidence: 99%